Explanatory models and coping with alcohol misuse among conflict-affected men in Ukraine - Sergiy Bogdanov; Kateryna Koss; Kimberly Hook; Quincy Moore; Catharina Van der Boor; Alessandro Masazza; Daniela C. Fuhr; Bayard Roberts; Carl May; Olha Fedorets; Oxana Bayer; Andrii Karachevskyy; et al. (SSM - Mental Health)
Affecting nearly 10% of men globally, alcohol use disorders (AUDs) represent a significant public health burden. Existing work, including from Ukraine, suggests that living in conflict settings may exacerbate the risk of AUDs. However, there is a dearth of evidence regarding alcohol misuse, as well as knowledge of factors associated with alcohol misuse patterns, in conflict settings. The aim of this qualitative study was to investigate explanatory models of alcohol misuse among conflict-affected men in Ukraine. Purposive and snowball sampling were used to recruit 66 conflict-affected men with alcohol misuse, family members of men who misuse alcohol, community health workers, and mental health and psychosocial support providers from locations across Ukraine. In the group of men who misuse alcohol (n = 25), we recruited individuals with diverse experiences of adversity: 1) internally displaced persons from eastern Ukraine and Crimea displaced after 2014; 2) Ukrainian military veterans or territorial defense volunteers from various regions; and 3) men living 5–15 km from the frontline. Semi-structured interviews were conducted in Ukrainian or Russian, and analysed using deductive and inductive analysis. Qualitative data received from each subgroup were analysed separately. The resulting explanatory model represents how Ukrainian conflict-affected men describe causes of alcohol misuse. Participants identified that alcohol misuse among Ukrainian men is often used as “self-treatment” to address mental health symptoms and feelings of demoralization that are exacerbated by a lack of supportive social environments and socio-economic problems; these behaviours also occur in an environment that deems alcohol misuse to be culturally appropriate. Family members and service providers offered a similar understanding of alcohol misuse as the men themselves. Strategies suggested by conflict-affected men to protect against alcohol misuse included engaging in alternative activities, finding supportive social environments, fear of negative consequences from alcohol misuse and increasing self-awareness and self-control. These findings indicate possible implications for interventions that target alcohol misuse among conflict-affected men, as well as demonstrate a need for developing culturally sensitive interventions that can address this unaddressed public health need.